Clinico-Pathological Study of Lung Carcinoma (Journal of Pathology of Nepal, 2014)
Background: Lung cancer is currently the most frequently diagnosed cancer in the world and the number one cause of cancer mortality worldwide.Materials and Methods: A descriptive study was conducted in 55 diagnosed lung carcinoma cases being treated in a Kathmandu based hospital over a period of 18 months from 22nd Oct. 2012 to 21st April 2014.Results: Out of total 55 lung carcinoma cases, 33 patients were male and 22 were female with Male: Female ratio of 1.5:1. The most frequent age group was 71-80 years. Lung cancer was more common among smokers (52.73 % of cases). Out of 47.27% non smokers, 76.92% were female. Squamous cell carcinoma was found to be the most common cancer type, comprising 63.64% of cases followed by adenocarcinoma (29.09% of cases) and small cell carcinoma (7.27% of cases). Among various diagnostic methods, CT guided Fine needle aspiration cytology (FNAC) and Pleural fluid cytology was found to be the best methods.Conclusion: Smoking showed a positive correlation among carcinoma of lung patients. Squamous cell carcinoma and adenocarcinoma were the most common tumors encountered among the smokers and non-smokers respectively. CT guided Fine needle aspiration cytology (FNAC) and Pleural fluid cytology yields the most diagnostic materials.DOI:  http://dx.doi.org/3126/jpn.v4i8.11496   Journal of Pathology of Nepal; Vol4, No.8 (2014) 623-625Background: Lung cancer is currently the most frequently diagnosed cancer in the world and the number one cause of cancer mortality worldwide.Materials and Methods: A descriptive study was conducted in 55 diagnosed lung carcinoma cases being treated in a Kathmandu based hospital over a period of 18 months from 22nd Oct. 2012 to 21st April 2014.Results: Out of total 55 lung carcinoma cases, 33 patients were male and 22 were female with Male: Female ratio of 1.5:1. The most frequent age group was 71-80 years. Lung cancer was more common among smokers (52.73 % of cases). Out of 47.27% non smokers, 76.92% were female. Squamous cell carcinoma was found to be the most common cancer type, comprising 63.64% of cases followed by adenocarcinoma (29.09% of cases) and small cell carcinoma (7.27% of cases). Among various diagnostic methods, CT guided Fine needle aspiration cytology (FNAC) and Pleural fluid cytology was found to be the best methods.Conclusion: Smoking showed a positive correlation among carcinoma of lung patients. Squamous cell carcinoma and adenocarcinoma were the most common tumors encountered among the smokers and non-smokers respectively. CT guided Fine needle aspiration cytology (FNAC) and Pleural fluid cytology yields the most diagnostic materials.DOI: 3126/jpn.v4i8.11496   Journal of Pathology of Nepal; Vol4, No8(2014)